2015
DOI: 10.4055/cios.2015.7.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Results between Hook Plate Fixation and Ligament Reconstruction for Acute Unstable Acromioclavicular Joint Dislocation

Abstract: BackgroundIn the present study, we aimed to compare clinical and radiographic outcomes between hook plate fixation and coracoclavicular (CC) ligament reconstruction for the treatment of acute unstable acromioclavicular (AC) joint dislocation.MethodsForty-two patients who underwent surgery for an unstable acute dislocation of the AC joint were included. We divided them into two groups according to the treatment modality: internal fixation with a hook plate (group I, 24 cases) or CC ligament reconstruction (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 29 publications
(33 reference statements)
6
70
1
1
Order By: Relevance
“…Regarding hook plate xation, the hook plays an important role in stabilization in ACJ dislocation, but the focused high pressure over the hook tip may cause erosion of bone cortex ( Figure 5). Among patients with hook plate xation, 25-50% suffer subacromial osteolysis or erosion [10,[19][20][21], which are the most common complications in hook plate xation. Subacromial osteolysis may result in more postoperative pain, discomfort, and an impaired functional outcome [9,10].…”
Section: Radiographic Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Regarding hook plate xation, the hook plays an important role in stabilization in ACJ dislocation, but the focused high pressure over the hook tip may cause erosion of bone cortex ( Figure 5). Among patients with hook plate xation, 25-50% suffer subacromial osteolysis or erosion [10,[19][20][21], which are the most common complications in hook plate xation. Subacromial osteolysis may result in more postoperative pain, discomfort, and an impaired functional outcome [9,10].…”
Section: Radiographic Outcomementioning
confidence: 99%
“…Among patients with hook plate xation, 25-50% suffer subacromial osteolysis or erosion [10,[19][20][21], which are the most common complications in hook plate xation. Subacromial osteolysis may result in more postoperative pain, discomfort, and an impaired functional outcome [9,10]. Yoon et al also reported a trend of an inferior functional score in patients with subacromial osteolysis [10], which indicated that greater stress on the hook tip may lead to a greater risk of subacromial osteolysis.…”
Section: Radiographic Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…xation are common procedures with good clinical outcomes. Although there exists comparative research regarding these two common surgical modalities in terms of postoperative outcome and complications [18,19], the treatment options remain under debate. Thus, the purpose of the present study was to compare these two common procedures with regards to functional outcomes and radiological outcomes in patients with acute advanced AC joint dislocation.…”
Section: Despite the Complications Both Loop Suspensory Reconstructimentioning
confidence: 99%
“…In a recent study, hook plate xation was reported to be a popular option that provides rigid xation and promotes nature scaring of the CC ligament, with the advantages of a simpler surgical technique, minimally-invasive access, and early resumption of normal activity [4,[10][11][12]. Despite these advantages, hook plate xation alsohas disadvantages, which include the need for implant removal surgery, subacromial impingement, subacromial osteolysis, and possible loss of reduction after implant removal, which may lead to complications such as a rotator cuff tear or an acromion fracture in patients with osteoporosis or those with a high activity level [13][14][15].…”
Section: Introductionmentioning
confidence: 99%